Heterogeneity of T cell receptor idiotypes in rheumatoid arthritis. - Brennan, F; Allard, S; Londei, M; Savill, C; Boylston, A; Carrel, S; Maini, R; Feldmann, M (1988)
The nature of the T cell response in the rheumatoid synovium was investigated by using monoclonals MX9 and 42/1C1, which recognize the V beta 8 and V beta 5 T cell receptor gene families respectively. The blood and synovial T cells of ten patients with rheumatoid arthritis were compared. The majority (8/10) had different numbers of V beta 5 and V beta 8 cells in the joints from those in the blood, indicating that the T cells in the joints were not a sample of those in the blood. In three patients both V beta 5 and V beta 8 cells in the joint were augmented in number, suggesting that the T cells selectively retained in the joint were not members of a single clone, but derived from many clones. Some patients had increased levels of V beta 5 or V beta 8 alone in the joint indicating that heterogeneity existed between patients. These results are not consistent with the preferential or dominant use of a single V beta gene family in the T cells involved in the rheumatoid arthritic joints.